Evaluation of Implementation of Dengue Hemorrhagic Fever Surveillance - Qurry Amanda; Fardhiasih Dwi Astuti; Ahmad Fadly (Disease Prevention and Public Health Journal, 2023)
Background: Dengue fever is still endemic in Indonesia. The government launched a DHF surveillance program. There was found some problems in the surveillance system, and the trend of dengue fever in 2016-2020 which had increased at the Pusat Kesehatan Masyarakat (Puskesmas) of Bantul II. This study aims to evaluate the implementation of DHF surveillance at the Puskesmas Bantul II. Method: This research is an evaluation of the CIPP model (Context, Input, Process, Product) with a qualitative-descriptive approach. This research was conducted in June-July 2021 at the Puskesmas Bantul II. Data was collected by interviewing 5 (five) informants. Results: The implementation of DHF surveillance at the Puskesmas Bantul II is based on input, human resources aren’t skilled epidemiologists, officers still hold concurrent positions, and haven’t received epidemiology/surveillance training. The infrastructure was complete, sufficient, and functioning properly. There is no specific allocation of funds for DHF surveillance. There are SOPs and surveillance guidelines, and DHF activities. Based on the process, the collection, processing, presentation, data analysis, and information dissemination have been carried out. The recommendations haven’t been implemented. The Health Office provides regular feedback, monitoring, and evaluation. Based on the output, reporting once a month on time. But its aren’t complete, some files are missing and damaged. Conclusion: The implementation of DHF surveillance at the Puskesmas Bantul II has been carried out, but several aspects of the input, process, and output do not match the indicators, so it affects the outcomes that are not in accordance with national standards.